Chemical diversity and therapeutic potentialities of seaweeds and marine sponges collected from the Red Sea: An update - Sally El Said Abo Halawa Abdelrahman, Mosad A. Ghareeb, Engy Mohsen, Ahmed A. Hamed, Seham El Hawary (Journal of Applied Pharmaceutical Science, 2023)
The marine environment is a vast and diverse ecosystem that is a valuable source of biologically active ingredients for the drug industry. For decades, natural products from marine organisms have been a major supplier of curative agents. Over 30,000 metabolites have been recorded from different marine organisms and associated microorganisms. Marine-derived compounds have diverse chemical structures, and biological and pharmacological applications, making them a promising platform for drug discovery from natural sources. This review highlights a comprehensive survey of the phytochemical and biological aspects of selected seaweed and marine sponges found in the Red Sea. These organisms, such as seagrass (Thalassia hemprichii) and marine sponges (Siphonochalina siphonella, Latrunculia magnifica, and Crella (Grayella) cyathophora), have been found to contain numerous chemical ingredients with therapeutic properties. Phenolic compounds in T. hemprichii have antioxidant and anticancer properties while marine sponges contain structurally diverse amides, alkaloids, terpenes, and steroids with cytotoxic, antiviral, and antimicrobial activities. The habitats of these organisms affect both the chemical components and their biological properties. These findings are encouraging and may be used in the development of new pharmaceuticals.
Keywords: Seaweed, marine sponges, marine natural products, bioactivities, Red Sea, drug discovery